Surgical Results in Pathological N1 Nonsmall Cell Lung Cancer - Yoshida, Yukihiro; Yotsukura, Masaya; Nakagawa, Kazuo; Watanabe, Hirokazu; Motoi, Noriko; Watanabe, Shun-ichi (The Thoracic and Cardiovascular Surgeon, 2020)
Background This retrospective study investigated the prognosis of patients with pathological N1 (pN1) nonsmall cell lung cancer (NSCLC).Methods We included patients with pN1 NSCLC who underwent lobectomy or pneumonectomy with mediastinal lymph node dissection and achieved complete resection (R0) between January 2000 and December 2012. Patients who received neoadjuvant therapy were excluded.Results A total of 249 patients were included. The mean age was 63.2 years, and 172 patients were males. Of the 249 patients, 200, 20, and 29 underwent lobectomy, bilobectomy, and pneumonectomy, respectively. The median observation period was 5.5 years. The 5-year overall survival (OS) rate was 64.6% (95% confidence interval: 58.3–70.4). Five-year OS rates were 79.8% for positive lymph nodes at station 13 or 14 (n = 57), 59.6% at station 12 (n = 72), 62.7% at station 11 (n = 69), and 56.9% at station 10 (n = 51) (log-rank test; p = 0.016); furthermore, the 5-year OS rate was 75.2% for patients with positive lymph nodes at a single station (n = 160) and 45.4% for patients with positive lymph nodes at multiple stations (n = 89) (log-rank test; p < 0.001). Five-year cumulative incidences of recurrence were equivalent between patients who received adjuvant chemotherapy and patients who did not (45.9 vs. 55.1%; Gray's test; p = 0.366). Distant recurrence was the most frequent mode of recurrence in both groups (70.8 and 67.3%).Conclusion The locations and the number of stations of the positive lymph nodes were identified as prognostic factors in patients with pN1 NSCLC. The primary mode of recurrence was distant recurrence irrespective of postoperative adjuvant chemotherapy.
Keywords: lung cancer; surgical treatment; chemotherapy; CT scan; pathology